THE ENRICHMENT OF BAKERY PRODUCTS FOR THE NUTRITION OF CHILDREN AND TEENAGERS - Mikhail Petrovich Mogilny; Diana Malikovna Mustafaeva (Современная наука и инновации, 2022)
The factors influencing the state of health of the population of the country are considered. In accordance with the Principles of state policy in the field of healthy nutrition, the causes and disorders of good nutrition were established. In solving the problem of improving the population of the country identified functional ingredients that affect the state of health, which can be used for the production of new fortified food products.